Administrative court practice / edited by Michael Supperstone QC and Lynne Knapman - QC, Michael Supperstone (ed.) (Oxford, 2008)
During the last three decades administrative law in the United Kingdom has been 1.01 transformed. In 1963 Lord Reid expressed the view that 'we do not have a devel oped system of administrative law'.' Indeed the third edition of Halsbury's Laws of England, published in 1959, still had no separate entry for administrative law. However, in 1981 Lord Diplock spoke of 'that towards a comprehensive progress system of administrative law' which he regarded as having been 'the greatest achievement' of the English courts in his judicial life-time.? A cursory glance at recent law reports indicates that developments are continuing unabated. The ambit of judicial review has expanded significantly in recent years. A remedy which was once limited to controlling the acts of central and local government now covers the activities of many non-governmental bodies and extends into the commercial world.